1957
DOI: 10.1063/1.1715877
|View full text |Cite
|
Sign up to set email alerts
|

Gel Dosimeter for Depth-Dose Measurements

Abstract: A chloral hydrate-agar gel has been used for depth-dose measurements with x-rays and electrons. HCl is formed from the chloral hydrate by the radiation and thus changes pH and electrical conductivity of the gel. Radiation beams can be visualized by adding an acid-base indicator. Quantitative measurements are made by spectrophotometry or by probing the gel with a pH electrode or a conductivity electrode pair. Spatial resolution of perhaps 0.2 mm has been obtained with conductivity electrodes. Doses of 2000 rad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 6 publications
0
24
0
2
Order By: Relevance
“…Gelatin dosimetry has been studied since 1950’s [62], [63], when the gel molecular proprieties began to be studied after ionizing radiation exposures. Some of these gelatins were used to prepare Fricke gel dosimeters, becoming the first dosimetric system able to three-dimensionally map the absorbed dose in a non-destructive and non-invasive manner [64][66].…”
Section: Introductionmentioning
confidence: 99%
“…Gelatin dosimetry has been studied since 1950’s [62], [63], when the gel molecular proprieties began to be studied after ionizing radiation exposures. Some of these gelatins were used to prepare Fricke gel dosimeters, becoming the first dosimetric system able to three-dimensionally map the absorbed dose in a non-destructive and non-invasive manner [64][66].…”
Section: Introductionmentioning
confidence: 99%
“…For example, dosimeters utilizing Fricke solution [6][7][8], polymers [9][10][11][12][13][14][15][16] and dyed plastics [17,18] have been successful in measuring radiation dose in three dimensions but not temporally. Electronic portal imaging devices (EPIDs) based on fluoroscopic [19,20] or solidstate radiation detection [21], as well as planar detector arrays [22] are capable of measuring radiation fields in two spatial dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…In 1957 Andrews and colleagues studied the dose distribution and measurements of the pH of sensitive gels by spectroscopy [6]. The use of these gels as a dosimeter began with Gore and colleagues in 1984 when it was investigated the Fricke gels, initially studied by Fricke and Morse in 1927, based on the principle of oxidation, and recorded the relaxation properties in nuclear magnetic resonance (NMR) and showed that the concentration of ferric ions could be quantified by this technique [7].…”
Section: Magic-f Gel Dosimetermentioning
confidence: 99%